Labour Market Dynamics and Worker Heterogeneity during the Great Recession: Evidence from Europe - Ronald Bachmann; Peggy Bechara; Anica Kramer; Sylvi Rzepka (Institute for the Study of Labor (IZA), 2015)
Using harmonized micro data, this paper investigates the effects of the early phase (2008-10) of the recent economic crisis on transitions between labour market states in Europe. Our analysis focuses on individual heterogeneity, on the type of employment contract, and on cross-country differences. Our analysis shows that specific worker groups, such as men and young persons, were particularly strongly hit by the crisis. Furthermore, more transitions from employment, and especially temporary employment to unemployment, were the main factor behind the rise in unemployment; while reduced unemployment outflows did not contribute substantially to the increase in unemployment during the early phase of the crisis.
Keywords: J6; E24; 330; recession; labour market transitions; Markov transition matrices; worker heterogeneity